Tribes of Odisha: Issues of social inclusion, exclusion and cultural assimilation - Mohapatra, Tanuja (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 16-33 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8043
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEyNi9ib2RoaS52NWkxLjgwNDM